Analisis Faktor Keterlambatan Proyek Konstruksi Gedung di Kabupaten Purworejo: Analysis of Delay Factors for Building Construction Project in Purworejo Regencey - Setyaning, Larashati B'tari; Nusantoro, Agung; Pratama, Sukma Adi (Jurnal Rekayasa Infrastruktur HEXAGON, 2024)
Basically, construction projects cannot be free from existing obstacles that can cause delays in ongoing projects. Work that experiences problems can cause delays and result in losses and various methods are taken to avoid problems that result in delays and losses. The aim of this research is to analyze the factors that cause delays in construction work on building construction projects in Purworejo Regency and analyze the correlation or relationship between these factors. In this research, data processing uses Exploratory Factor Analysis (EFA) analysis for correlation or relationship between factors causing delays in building construction projects in Purworejo Regency. A set of questionnaires was used to obtain the required primary data. Exploratory factor analysis techniques are used to identify existing latent variables. Questionnaires were obtained from 40 people consisting of contractors, supervisory consultants and owners involved in this research. The results of the research explain that five factors influence delays in building construction projects in Purworejo Regency, namely auction process factors and non-technical events, inappropriate technical planning, accuracy factors in the amount of material sent, communication and coordination factors, equipment productivity factors.